ANALYSIS OF TEACHER COMMUNICATION COMPETENCE IN DEALING WITH STUDENTS WITH SPECIAL NEEDS - Arya Prasetya (International Journal of Teaching and Learning, 2024)
This research focuses on analyzing teachers' communication competencies in dealing with students with special needs, with the aim of understanding the extent of teachers' abilities in carrying out effective communication that supports an inclusive learning process. This research uses a literature review approach to obtain an in-depth picture of the perspectives, strategies and challenges faced by teachers in communicating with students with special needs. The research results show that the majority of teachers have a high awareness of the importance of effective communication competencies in supporting the success of students with special needs. However, there are still obstacles in its implementation, such as a lack of specific training and preparation regarding appropriate communication techniques for students with special needs. Apart from that, the research results also show that the adaptation of communication methods used by teachers is very dependent on the type of special needs that students have. This reflects the importance of an individualization approach in teacher communication strategies. The recommendations put forward include strengthening capacity through regular training for teachers in effective and inclusive communication techniques, as well as implementing adequate support systems to facilitate the communication needs of students with special needs. It is hoped that with a better understanding of effective communication competencies, teachers can be more efficient in supporting successful learning for all students, especially those with special needs.